Medicinal plants' hosting ability for nematode Meloidogyne javanica and M. incognita - Baida, Fernando Cesar; Santiago, Débora Cristina; Vidal, Luiz Henrique Ilkiu; Baida, Luiz Carlos [UNESP]; Stroze, Camila Torres (My University, 2011)
Medicinal plants can be attacked by pests, diseases and nematodes, which can compromise the quality and quantity of their healing properties and their yield. The aim of this study was to analyse the reaction of 15 medicinal plant species to the nematode Meloidogyne spp. The seedlings were produced by seed germination or cuttings under greenhouse conditions. A completely random experimental pattern of 15 treatments and 10 replications was chosen for the study. The seedlings were inoculated with approximately 5000 eggs + J2/plant 20 days after planting. Plant height and fresh and dry leaf weight, were measured 60 days after planting. The roots were collected, thoroughly washed and stained with Philoxine B and then processed to extract the eggs to determine the reproduction factor. For M. incognita the results showed that Chamomile was susceptible with RF = 1,64 making it a good host, and the other plants were resistant (RF < 1), and for M. javanica that all the plants showed resistance (RF < 1), Myrrh, Rue and Balsam demonstrating immunity (RF = 0).
Keywords: Galls; Parasitism; Reaction; Reproduction factor